The effect of learning motivation, facilities, and materials on understanding and attitude forming through online learning - Subekan, Achmat; Azwar, Azwar (Cendikia : Media Jurnal Ilmiah Pendidikan, 2024)
This study aims to determine the effect of learning motivation, learning facilities, and learning materials on students' understanding and attitudes through online learning. The research method used is quantitative with data processing using structural equation modeling (SEM). The results showed that the independent variables in the form of motivation, learning facilities, and learning materials had an influence on the understanding variable with different levels. Motivation has a positive and significant effect on the emergence of understanding. Likewise, the learning material variable has a positive and significant effect on the understanding of the learner participants. Meanwhile, learning facilities do not have a significant effect on understanding. In the next stage, the understanding variable has a positive and significant influence on the formation of participants' attitudes. This is in accordance with the expected goal in the activities of the Ministry of Finance for One State, the emergence of a generation that has great concern for state finances in the future. Among the three independent variables studied, the learning material variable has the greatest influence on the formation of a good understanding and the emergence of a positive attitude towards state finances. This variable is able to give the greatest influence on the participants' understanding until it finally has an impact on their positive attitude towards state finances. This also shows that the learning materials provided in the activities of the Ministry of Finance of the Republic of Indonesia are appropriate, according to the needs of the participants so that they have the greatest influence on the understanding and formation of participants' attitudes.